Learning Cycle 7E Terintegrasi Potensi Lokal Ekosistem Mangrove Untuk Meningkatkan Berpikir Kritis Peserta Didik: (Learning Cycle 7E integrates the local potential of mangrove ecosystem to improve students' critical thinking) - Ningrum, Tri Yanti Sulistriaji; Habibi, Habibi; Azizah, Lutfiana Fazat (BIODIK, 2023)
Meaningful Biological teaching and learning can make students critically recognize themselves and their environment. The local potential of the community needs to be introduced to students, for example in Kalianget District, Sumenep Regency, one of the local potentials is the mangrove ecosystem and salt ponds. Local potential can be integrated into learning through student work sheet (LKPD). This study aimed to determine the validity and effectiveness of Learning Cycle 7E integrated with the local potential of the mangrove ecosystem in improving students' critical thinking. The type of research was 4D model development research, namely the define, design, and development stages without the dissemination stage. The trial design used a pretest-posttest control group design. As the result of research, the product validity is very feasible with 98%score. Product readability is easy to read with 81% score. The result of the gain score indicate an increase in learning in the experimental class by 0.85 (high) compared to the control class by 0.51 (medium). The effectiveness of the product is very effective in increasing students' critical thinking by obtaining a Sig (2-tailed) value of less than 0.05 using the independent sample t-test test which proved that there is a difference in critical thinking between the experimental class and the control class. The practicality of the product is very practical with 97% score. Key words: Learning Cycle 7E, Local Potential, Critical Thinking, 4D Model Abstrak. Pembelajaran IPA yang bermakna dapat membuat peserta didik secara kritis dapat mengenali diri dan lingkungannya. Potensi lokal perlu diperkenalkan kepada peserta didik, misalnya di Kecamatan Kalianget Kabupaten Sumenep salah satu potensi lokalnya adalah ekosistem mangrove dan tambak garam. Potensi lokal dapat diintegrasikan ke dalam pembelajaran melalui LKPD. Penelitian ini bertujuan untuk mengembangkan LKPD Learning Cycle 7E terintegrasi potensi lokal ekosistem mangrove dalam meningkatkan berpikir kritis peserta didik. Jenis penelitian yang digunakan adalah penelitian pengembangan model 4D yaitu tahap define, design, development tanpa tahap disseminate. Adapun desain uji cobanya menggunakan pretest-postest control group design dilakukan pada 22 peserta didik kelas VIII di SMPN 2 Kalianget, Sumenep. Hasil penelitian untuk validitas produk adalah sangat layak dengan memperoleh skor 98%. Keterbacaan produk adalah mudah dibaca dengan mendapatkan skor 81%. Hasil gain score menunjukkan adanya peningkatan pembelajaran di kelas eksperimen sebesar 0,85 (tinggi) dibandingkan kelas kontrol sebesar 0,51 (sedang). Efektivitas produk adalah sangat efektif meningkatkan berpikir kritis peserta didik dengan memperoleh nilai Sig(2-tailled) kurang dari 0,05 menggunakan uji independent sample t-test yang membuktikan terdapat perbedaan berpikir kritis antara kelas eksperimen dan kelas kontrol, serta kepraktisan produk adalah sangat praktis dengan skor 97%. Kata kunci: Learning Cycle 7E, Potensi Lokal, Berpikir Kritis, Model 4D